Synergistic Flame Retardancy of Polyamino Cyclotriphosphazene and 1,3,5-tris(2-Hydroxyethyl)cyanurate in Polypropylene - Tang, Linsheng; Wang, Yuchong; Li, Li; Wang, Yong; Song, Hongbing (Asian Journal of Chemistry, 2015)
In this paper, the synergistic flame retardancy of polyamino cyclotriphosphazene and 1,3,5-tris(2-hydroxyethyl)cyanurate in polypropylene was studied by limiting oxygen index measurement, vertical burning test and cone calorimeter test. Thermal stability of flame retarded polypropylene (FR-PP) was investigated by thermogravimetric analysis and the mechanism was discussed by the residue analysis obtained in cone calorimeter test. The results showed that there was an excellent synergistic flame retardancy between polyamino cyclotriphosphazene (PHACTPA) and 1,3,5-tris(2-hydroxyethyl)cyanurate (THEIC) in polypropylene, which resulted in the increased limiting oxygen index, improved vertical burning class and reduced total heat release, peak heat release rate, the mean heat release rate, mean effective heat of combustion and mean mass loss rate. For example, the flame retarded polypropylene alone with 20 wt. % polyamino cyclotriphosphazene or 1,3,5-tris(2-hydroxyethyl)cyanurate based on the total weight of the composites had the limiting oxygen index of 25.2 and 18.7 %, respectively and did not pass UL94-0 class of the burning test, while the flame retarded polypropylene with 20 wt. % the combination consisted of 65 wt. % polyamino cyclotriphosphazene and 35 wt. % 1,3,5-tris(2-hydroxyethyl)cyanurate had the limiting oxygen index of 27.4 % and passed UL94-0 class. The thermogravimetric results indicated polyamino cyclotriphosphazene or polyamino cyclotriphosphazene/1,3,5-tris(2-hydroxyethyl)cyanurate improved the thermal stability of polypropylene. The residues obtained in cone calorimeter test showed that polyamino cyclotriphosphazene/1,3,5-tris(2-hydroxyethyl)cyanurate played a flame retardancy by a condensed phase mechanism. The polyamino cyclotriphosphazene was decomposed into non-volatile phosphoric acid compounds such as phosphoric acid, metaphosphoric acid and polyphosphoric acid in the process of combustion, which promoted the carbonization of polypropylene and inert gases such as CO2, N2 released from the thermal decomposition of polyamino cyclotriphosphazene, polypropylene and 1,3,5-tris(2-hydroxyethyl)cyanurate made the char layer foaming, the formed intumescent layer resulted in flame retardancy by the barrier effect on heat, air and decomposition products. Combining 1,3,5-tris(2-hydroxyethyl)cyanurate promoted the decomposition of polyamino cyclotriphosphazene to phosphoric acid compounds, so improved the charring of polypropylene and resulted in excellent synergistic flame retardancy.